2009
DOI: 10.1590/s0044-59672009000100026
|View full text |Cite
|
Sign up to set email alerts
|

Gram-scale isolation of isobrucein B and neosergeolide from Picrolemma sprucei Hook. f.

Abstract: Quassinoids neosergeolide and isobrucein B, obtained from Picrolemma sprucei, have proven in vitro antitumor, antimalarial, anthelminthic, cytotoxic, insecticide and leishmanicidal activities. There is interest in the in vivo pharmacological study of these natural compounds and their semi-synthetic derivatives, however, the quantities obtained in previous extraction processes have been shown to be a limiting factor for continuation of these studies. Herein, we describe a method for obtaining grams of these qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…A detailed procedure for extraction and isolation of 1 on a gram scale has been previously published. 44 Briefly, this procedure consists of pilot-scale degreasing by Soxhlet extraction with hexanes of the dried, ground roots and stems of P. sprucei. The plant materials were further extracted with water in a Soxhlet apparatus.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A detailed procedure for extraction and isolation of 1 on a gram scale has been previously published. 44 Briefly, this procedure consists of pilot-scale degreasing by Soxhlet extraction with hexanes of the dried, ground roots and stems of P. sprucei. The plant materials were further extracted with water in a Soxhlet apparatus.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Ultrapure water, obtained from a Milli-Q Plus System (Millipore, Bedford, MA, USA), was used in all analyses. 1 and 2 were isolated from P. sprucei as described previously 11,19 and used as reference standards. Their identity and purity were established based on 1D and 2D NMR, IR, HR-ESI-TOF-MS, HPLC-DAD and LC-ESI-MS analyses and comparison to literature data.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…These compounds have been isolated previously from the stems and roots of P. sprucei on a milligram scale 10 and more recently on a gram-scale. 11 Also, 1 has been isolated from the leaves of this plant. 12 Recently, the antimalarial, antileukemic, antifeedant and leishmanicidal activities of 1 were the subject of a review.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show promising results for the antiplasmodial activity of the family Simaroubaceae against P. falciparum species . More specifically, it was found that the quasinoides simalikalactone E and D, eurycomanone, isobrucein B, among others, are the most active metabolites present in these plants [ 38 , 39 , 42 44 ]. This group of active metabolites is considered a taxonomic marker of this plant family, since it is the most abundant group of natural metabolites that they possess and their synthesis is almost exclusive compared to other plant families.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous compounds have been isolated from this family, such as quassinoids, alkaloids, triterpenes, steroids, coumarins, anthraquinones, flavonoids and other metabolites [ 55 – 58 ]. Most of the studies reported for the Simaroubaceae family show antiplasmodial activity for the quassinoids extracted from these plants [ 35 , 38 40 , 42 , 44 ], with characteristics of highly active compounds [ 20 ]. Quassinoids such as isobrucein B and sergolides isolated from P. huberi extracts have only been evaluated in a melanoma cell line, and in colon and lung cell lines, with sergolide having a higher cytotoxicity CC 50 in a range of 10 −7 –10 −8 M [ 45 ].…”
Section: Discussionmentioning
confidence: 99%